A 5-min paradigm to evoke robust emotional reactivity in neuroimaging studies - Sabatinelli, Dean; Winker, Constantin; Farkas, Andrew H.; Rehbein, Maimu A.; Junghoefer, Markus (Frontiers in Neuroscience, 2023)
The advent of the Research Domain Criteria (RDoC) approach to funding translational neuroscience has highlighted a need for research that includes measures across multiple task types. However, the duration of any given experiment is quite limited, particularly in neuroimaging contexts, and therefore robust estimates of multiple behavioral domains are often difficult to achieve. Here we offer a “turn-key” emotion-evoking paradigm suitable for neuroimaging experiments that demonstrates strong effect sizes across widespread cortical and subcortical structures. This short series could be easily added to existing fMRI protocols, and yield a reliable estimate of emotional reactivity to complement research in other behavioral domains. This experimental adjunct could be used to enable an initial comparison of emotional modulation with the primary behavioral focus of an investigator’s work, and potentially identify new relationships between domains of behavior that have not previously been recognized.